Production of dicalcium phosphate anhydrous from the bone of Nile Tilapia (Oreochromis niloticus) grown in Viet Nam - Khanh Nguyen Ngo; Kien Quoc Le; Lien Huong Huynh; Van Dat Nguyen; Viet Nhan Hoa Nguyen; Quoc Phong Ho (CTU Journal of Innovation and Sustainable Development)
This study was conducted to find a facile method for preparing dicalcium phosphate anhydrous (DCPA) from the bones of Nile Tilapia, recovered from a by-product of the fillet process. The by-product containing bones of the Nile Tilapia collected from a local factory was stewed in boiling water and treated with NaOH solution to remove organic impurities from the obtained bones of Tilapia. The pre-treated bones were then calcined and ground to a fine powder before converting to dicalcium phosphate anhydrous. The factors affecting the yield of DCPA such as precipitation pH, reaction temperature, and reaction time were investigated. Modern analytical methods, such as XRD, SEM, XRF, and TGA were employed to characterize the DCPA. The DCPA product with high crystallinity (~ 98.5%) with particle sizes ranging from 1 to 3 µm was obtained at pH 5, 90 min. reaction, and 80°C. This study showed a facile and viable method for producing dicalcium phosphate anhydrous from the bones of Nile Tilapia.